Present-Day and Future Global Bottom-Up Ship Emission Inventories Including Polar Routes - Paxian, Andreas; Eyring, Veronika; Beer, Winfried; Sausen, Robert; Wright, Claire (Environmental Science & Technology, 2010)
We present a global bottom-up ship emission algorithm that calculates fuel consumption, emissions, and vessel traffic densities for present-day (2006) and two future scenarios (2050) considering the opening of Arctic polar routes due to projected sea ice decline. Ship movements and actual ship engine power per individual ship from Lloyd’s Marine Intelligence Unit (LMIU) ship statistics for six months in 2006 and further mean engine data from literature serve as input. The developed SeaKLIM algorithm automatically finds the most probable shipping route for each combination of start and destination port of a certain ship movement by calculating the shortest path on a predefined model grid while considering land masses, sea ice, shipping canal sizes, and climatological mean wave heights. The resulting present-day ship activity agrees well with observations. The global fuel consumption of 221 Mt in 2006 lies in the range of previously published inventories when undercounting of ship numbers in the LMIU movement database (40,055 vessels) is considered. Extrapolated to 2007 and ship numbers per ship type of the recent International Maritime Organization (IMO) estimate (100,214 vessels), a fuel consumption of 349 Mt is calculated which is in good agreement with the IMO total of 333 Mt. The future scenarios show Arctic polar routes with regional fuel consumption on the Northeast and Northwest Passage increasing by factors of up to 9 and 13 until 2050, respectively.